Racialization and Subsidized Low-Income Housing in American Cities. Issue 2 (23rd February 2019) - Blackmond Larnell, Twyla; Williams, Cameron
ABSTRACT: Historically, the racialization of minority groups' housing needs shaped policy decisions and provoked the unequal distribution of subsidized low-income housing across American neighborhoods and cities. This study extends beyond the Black–White dichotomy in the literature to examine variations in cities' availability of all federally subsidized low-income housing units (public housing, multifamily, and Housing Choice Voucher) according to which racial group (White, Black, Latinx, and Asian) constitutes the majority population. The results of quantile regression analyses indicated that majority-Black cities possess considerably more subsidized housing units than other cities whereas majority-Asian and majority-Latinx cities experienced reduced access to the housing units.